POTENTIAL IMPACT OF CARBON TAX IMPLEMENTATION ON THE AGRICULTURE SECTOR IN INDONESIA, SPECIFICALLY THROUGH CARBON TAX IMPOSITION ON ENERGY USE - Syahrituah Siregar1*, Luthfy Fatah2, M. Handry Imansyah2, Sunardi2, (Chelonian Research Foundation, 2024)
Indonesia has agreed to comply with the Paris Agreement, which includes a commitment to restrict and control emissions of greenhouse gases (GHGs). The commitment is reinforced by the submission of the Enhanced NDC document mandating the higher emission reduction target in each scenario. The instrument of carbon pricing to implement soon is carbon tax, which is applied to emissions resulting from energy consumption. The agriculture sector, a substantial component of Indonesia’s economy, is experiencing growth as a result of revitalization through mechanization revolution leading to a heightened reliance on energy consumption. These arguments indicate that although the carbon tax is a component of Indonesia’s efforts to decrease greenhouse gas emissions, its impact on the agriculture sector must be cautiously controlled. The objectives of this study are to: 1. Estimate the potential revenue from carbon tax across all sectors, including agriculture; 2. Estimate the impacts of implementing carbon tax on the performance of the agriculture sector, including output, employment, and income levels. The result shows that the potential carbon tax revenue in Indonesia from all economic sectors is IDR 5,025,641,983,076.-. The agricultural sector has the potential to generate tax revenues of IDR 418,242,180.-. These are vary small compared to others’ most practices. There is a potential decline in the level of agricultural sector output of IDR 16,366.3 million and employment of 17,884,082 workers. At the subsector level, the largest decline for both indicators occurred in the Non-edible crops subsector. In terms of income, there is a potential decline as much as IDR.26,656.76 million. The distribution pattern of income reduction between classes due to the tax burden tends to be progressive. On the other hand, the intensity of income decline in each class tends to be regressive. Thisresults recommend that there should be mitigation in implementing the carbon tax in Indonesia using any appropriate strategies. Keywords: agriculture, carbon tax, output, employment, income, regressive